2013
DOI: 10.1055/s-0033-1343501
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Rehabilitation of Facial Nerve Injury: A Review of the Literature

Abstract: Currently, techniques have been attempted to achieve adequate dynamic facial reanimation of the paralyzed facial nerve. Despite the advances that have occurred in the last few years, it has been classically very difficult to achieve a House-Brackmann grade better than grade III. Outcomes are improving. Ultimately, the approach depends on the surgeon's experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
(64 reference statements)
0
10
0
Order By: Relevance
“…The IP group was used as the positive control because this technique has consistently been shown in the literature to be a reliable means of reinnervating muscles when primary nerve repair is not possible. [9][10][11][12][13] Successful reinnervation prevents muscle atrophy and allows the return of function, as demonstrated by the recovery of vibrissae movement and snout symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…The IP group was used as the positive control because this technique has consistently been shown in the literature to be a reliable means of reinnervating muscles when primary nerve repair is not possible. [9][10][11][12][13] Successful reinnervation prevents muscle atrophy and allows the return of function, as demonstrated by the recovery of vibrissae movement and snout symmetry.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have noted that facial reanimation using dynamic surgical techniques achieve better results than static operations but are often associated with higher risk of failure due to the complexity of the procedure [15, 16]. We found that facial reconstruction with single-stage dynamic muscle support techniques rarely achieved resting facial symmetry, and many patients later underwent subsequent reoperations for incomplete correction or malfunction of correction.…”
Section: Discussionmentioning
confidence: 87%
“…Despite advances in surgical techniques, facial reanimation seldom exceeds a House-Brackmann grade greater than grade III. 1-3…”
Section: Introductionmentioning
confidence: 99%